OPTIMISASI PORTOFOLIO CAMPURAN - , CHANDIKA HANDAYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Stock is one instrument that is often used in investment. The rate of expected return of shares and amount of risk borne by the investor are things that need attention. To optimize returns and minimize the risk of a stock portfolio can be formed. Return is calculated from the monthly closing price on each of the assets listed on the NASDAQ-100. Optimization mixed portofolio is a combination of risky assets and a risk free asset with the highest Sharpe ratio, known as tangency portfolio. Risk assets are assets that the future rate of return aktualnyaa still contains uncertainties, such as stocks. Risk-free asset is an asset that level of return in the future can already be determined at this time,such as Treasury Bills.